Trajetória imigrante, fronteira e república: entre a enxada, o caderno e a cruz (1848-1930) - Kemmerich, Ricardo (2023)
The theme of the thesis is related to the processes of construction, consolidation of national states and European migrations, and aims to understand the process of cultural integration, which is expressed in politics and in the religiosity of immigrants of Italian origin, especially from Veneto, when during the First Republic (1889 – 1930) in southern Brazil in a context of border experience. For a long time, the historiography about immigration in Rio Grande do Sul has demystified the idea that the society of immigrant origin was averse to Italian nationalism, politically apathetic, without political engagement or as an electoral mass subservient to the ruling political classes in the State. The justification for such an understanding would, to a large extent, be due to the majority peasant origin of the Italian Veneto region, whose culture is described as markedly peaceful, orderly and with a very strong Catholic religiosity. This thesis works with a demystifying perspective. The frontier experience, as an experience of differentiation and integration, was a permanent phenomenon in migratory processes. The problems related to the process of construction of the Italian identity linked to the formation of the Italian State and the consequent secularization of society provoked ruptures in the traditional references of identification and social organization that were re-signified in the Americas. This Thesis has as its object the written testimonies of Giulio Lorenzoni (1863-1934) Antônio Ceretta (1868 – 1943) and Andrea Pozzobon (1863 – 1944) as a basis for reflection and analysis of this process of political and cultural integration. As a methodological approach, it was decided to use their testimonies as a guideline for the construction of the historical trajectory of this moment of transformation. From this it was possible to understand that, before a political apathy and the conformation of national and religious identities, this generation of immigrants was inserted in a moment of rupture between modernity and tradition that was characterized by the emergence of new practices of organization and identification social, that is, a moment of political learning that took place within the project of modernization of the States. In Rio Grande do Sul, these new practices together with new forms of sociability will be of paramount importance for the processes of political and cultural integration. The narrative that guided our analysis begins with the process of building the Italian national State, prologue of learning and political integration into the modern world, extending to the first decades of the 20th century in the communities that made up the Colônia Silveira Martins, the fourth Imperial colony implemented in from 1877. The history of the process of this integration of the region today called Quarta Colônia will sometimes be confronted with the history of other nuclei that were formed in the same period from documental and bibliographical sources gathered and consulted in Brazil and Italy. This Doctoral thesis is part of the History, Culture and Power area of concentration along with the Frontier, Politics and Society Research Line of the Graduate Program in History at UFSM and was supported and financed by CAPES, with a doctoral scholarship Demanda Social and Sandwich Scholarship with the Ca'Foscari University of Venice between September 2019 and March 2020 during the beginning of the Covid 19 Pandemic.